Mobile ticketing using Bluetooth low energy technology - João Pedro Norim Marques Bandeira (2017)
Public transport play an important role in most cities, and even more in large cities. Over the last few years, we've seen some cities taking measures in order to reduce the number of cars on the streets, and make people use public transportation. This evolution of the way people commute and move around cities, associated with the technological evolution of current times, would benefit from a solution that could motivate more people to use public transports, by making the ticketing and validation processes easier and simpler. The fast spread of mobile payment solutions, and its acceptance by the population, provide an opportunity to apply this idea to public transportation. The solution this thesis proposes will also take advantage of Bluetooth Low Energy (BLE) beacons, which are currently compatible with most mobile devices (with Bluetooth capabilities), and are expected to become even more accessible and with better performance in a near future. The solution presented is a platform which the users access via an application on their mobile devices, and that is integrated in an intermodal public transportation network (including bus, light rail and train) that works as a check-in/be-out system. The way the mobile application works is by using the Bluetooth technology on the smartphones to detect BLE beacons, which are installed in the vehicles (buses) or stations (light rail and train), and that allow the tracking of the users' trips from start to end. This platform also suggests the implementation of post-billing with the integration of a tariff optimization algorithm based on each user's monthly trips. This process requires minimal input from all the parties involved, resulting in a smoother experience either for the user, and for the transport operators, making public transportation more appealing to everybody. The main focus of this work is to evaluate of the viability of the use of BLE beacons in real world scenarios, where all wireless communications are subject to interferences by other devices. Besides the description of a platform that takes advantage of the use of BLE beacons as part of a mobile ticketing system, also the challenges of the process, along with the testing methodologies and results are described. The validation of the solution is integrated in a pilot study conducted in Porto.